(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Concrete and steel are extensively utilized construction materials with an ever-increasing demand. The construction sector alone consumes approximately 75% of the total raw materials, resulting in significant strain on natural resources and considerable environmental impact. Moreover, construction materials contribute substantially to global CO2 emissions. Steel and in-situ concrete are dominant materials in commercial construction, making their production and usage highly influential in environmental terms due to the sheer quantity involved. Furthermore, the escalating energy costs and potential future shortages have heightened the importance of considering both embodied energy (energy consumed during production) and operational energy (energy utilized over the projected lifespan) for construction materials. Consequently, builders, designers, and building owners are increasingly emphasizing these energy aspects.A prevailing global trend, including in India, is to adopt eco-friendly designs. Consequently, the concrete and steel industries have made substantial efforts in recent years to position their materials as optimal solutions for sustainable building design. Given that sustainable practices necessitate minimizing natural resource consumption, reducing air emissions, and optimizing embodied energy, this study aims to compare and quantify these factors to evaluate the disparities between concrete and steel frame structures in terms of their construction requirements.